Strategic Utilization of Muhammadiyah’s Waqf Land Assets To Support Green Economy - Setiyowati, Arin; Salsabilla, Salma Nadia; Berkah, Dian; Nadid, Erdin (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: The utilization of waqf land assets, especially in the Muhammadiyah Organization, has not been optimal in supporting sustainable development and a green economy. A strategy for utilizing waqf land assets in the Muhammadiyah Organization to support a green economy is pivotal. Methods: This study used a qualitative method with a case study approach. The sources used in this study are primary and secondary data. The data analysis technique used in this study was simplifying raw data from interviews or data reduction. Results: Data collection used in-depth interviews with Nadzir administrators. Based on the interviews, four main detailed themes emerged: management of waqf land assets, utilization of waqf land for a green economy, collaboration and partnership, and challenges and optimization strategies. These four themes provide a complete picture of how the waqf land management process works in the field practice. Conclusion and suggestion: Optimizing the use of waqf land assets by Muhammadiyah, especially in Bojonegoro and Lamongan, has shown a paradigm shift from traditional waqf management to productive waqf oriented towards sustainability through integration with the concept of green economy.